Nab-Paclitaxel-based induction chemotherapy with or without cetuximab for locally advanced head and neck squamous cell carcinoma. (September 2017) - Adkins, Douglas; Ley, Jessica; Oppelt, Peter; Wildes, Tanya M.; Gay, Hiram A.; Daly, Mackenzie; Rich, Jason; Paniello, Randal C.; Jackson, Ryan; Pipkorn, Patrik; Nussenbaum, Brian; Trinkaus, Kathryn; et al.
Highlights: Similar efficacy with cetuximab added to induction chemotherapy followed by CRT. Similar deliver of induction chemotherapy and CRT with addition of cetuximab. Similar adverse events with cetuximab, except more rash. Abstract: Objectives: To explore the effect of incorporating cetuximab into induction chemotherapy in locally advanced head and neck squamous cell carcinoma (HNSCC). Materials and methods: Retrospective comparative analysis of two consecutive prospective phase II trials was performed: trial 1 with nab -paclitaxel/cisplatin/5-FU and cetuximab (APF-C; n = 30) and trial 2 with APF (n = 30). Patients were scheduled to receive chemoradiation therapy (CRT) with cisplatin. T2-4 classification oropharynx (OP)/larynx/hypopharynx SCC were included. Cumulative incidence of death of disease (CIDD), overall survival (OS), and cumulative incidence of relapse were compared between APF-C and APF. Results: No significant differences in patient or tumor characteristics were noted between the groups. Median follow-up of surviving patients was 52 (25–95) months. Relapse occurred in 5 (17%) patients treated with APF-C and in 2 (7%) treated with APF (p = 0.37). In human papillomavirus (HPV)-related OPSCC (n = 34), the CIDD at 52 months was 3.4% with APF-C and 2.6% with APF and the two-year OSs were 94%. In HPV-unrelated HNSCC (n = 25), the CIDD at 52 months was 4.4% with APF-C and 3.3% with APF and two-year OSs were 83% and 92%, respectively. CIDD or OS did not differ when stratified by treatment group and HPV status (CIDD: p = 0.80; OS: p = 0.30). Conclusion: This exploratory retrospective comparative analysis demonstrated no significant difference in CIDD, OS, or cumulative incidence of relapse between patients treated with APF-C or APF.